Experimental study of bedforms obtained with floating particles in a pipe flow. (20th January 2015) - Edelin, D.; Josset, C.; Castelain, C.; Fayolle, F.
Abstract: We investigate experimentally the formation of bedforms caused by the sustained flow of water and solid particles in a circular pipe ( =30 mm ). The special feature of the tests carried out was the use of floating particles ( d=756 μm, ρ_s=907 kg m^-3 ) whereas bedforms are usually studied with sedimental materials. A closed loop was used, so that the solid flux could be maintained for an infinite time. The finite size of the tube led to the saturation of the growth of the vortex ripples produced. For the set of parameters studied, the threshold of motion was obtained within a range of laminar to low turbulent flow. The saturated state was studied to characterise it for different flow rates and solid loads. The frequency, wavelength and propagating velocity of ripples were determined using different methodologies based on image analysis and pressure analysis. The frequency and propagating velocity show a clear linear dependence on the initial Shields number, while the wavelength seems to be constant in our experiments.